ExaFEL: extreme-scale real-time data processing for X-ray free electron laser science - Blaschke, Johannes P.; Bolotovsky, Robert; Brewster, Aaron S.; Donatelli, Jeffrey; DuJardin, Antoine; Feng, Wu-chun; Ganapati, Vidya; Kroeger, Wilko; Mendez, Derek; McCorquodale, Peter; Mirchandaney, Seema; O'Grady, Christopher P.; et al. (Frontiers in High Performance Computing, 2024)
ExaFEL is an HPC-capable X-ray Free Electron Laser (XFEL) data analysis software suite for both Serial Femtosecond Crystallography (SFX) and Single Particle Imaging (SPI) developed in collaboration with the Linac Coherent Lightsource (LCLS), Lawrence Berkeley National Laboratory (LBNL) and Los Alamos National Laboratory. ExaFEL supports real-time data analysis via a cross-facility workflow spanning LCLS and HPC centers such as NERSC and OLCF. Our work therefore constitutes initial path-finding for the US Department of Energy's (DOE) Integrated Research Infrastructure (IRI) program. We present the ExaFEL team's 7 years of experience in developing real-time XFEL data analysis software for the DOE's exascale supercomputers. We present our experiences and lessons learned with the Perlmutter and Frontier supercomputers. Furthermore we outline essential data center services (and the implications for institutional policy) required for real-time data analysis. Finally we summarize our software and performance 1 ExaFEL engineering approaches and our experiences with NERSC's Perlmutter and OLCF's Frontier systems.